Neotropical bats that co-habit with humans function as dead-end hosts for dengue virus - Vicente Santos, Amanda (2017)
This work was supported by FEESCONARE VI-803-B4-656, the Graduate Studies System Fund of the University of Costa Rica (SEPFR-082), and the Incentive Fund from the Postgraduate Studies Program of the National Council for Scientific and Technological Research (CONICIT)